The use of platelet-rich plasma in the healing of chronic and hard-to-heal wounds – a systematic review - Pawłowska, Paulina; Piosik, Szymon; Skorupa, Aleksandra; Piasecki, Łukasz; Dudziak, Natalia; Kochański, Marek (Journal of Education, Health and Sport, 2026)
INTRODUCTION: Chronic wounds are a significant clinical problem, burdening healthcare systems and affecting the quality of patients’ life. The healing of chronic wounds is impaired at multiple levels, which makes traditional treatment methods often insufficient. Platelet-rich plasma is an autologous blood-derived preparation containing a high concentration of platelets and growth factors that can modulate regenerative processes in damaged tissues. OBJECTIVE: The objective of this review is to evaluate the efficacy and safety of using PRP in treatments of chronic and hard-to-heal wounds based on current clinical data. MATERIALS AND METHODS: A systematic search of the PubMed, Scopus, and Web of Science databases was conducted to identify clinical studies. Randomized controlled trials, cohort studies, case series, and systematic reviews published up to December 2025 were analyzed. Inclusion criteria included studies involving adult patients with chronic wounds, diabetic ulcers, pressure ulcers, venous ulcers, and hard-to-heal postoperative wounds. The following parameters were evaluated: wound healing time, rate of complete wound closure, reduction of wound surface area, pain intensity and the occurrence of adverse effects. KEY RESULTS: The analysis, covering 29 randomized clinical trials involving 2,198 chronic wounds, showed that the use of platelet-rich plasma significantly increased the chances of complete wound closure compared to standard treatment, with an odds ratio of 5.32 (95 percent CI: 3.37 to 8.40). Furthermore, PRP therapy was associated with a reduction in wound healing time by an average of 25 to 35 percent and a significant reduction in wound surface area. CONCLUSIONS: Platelet-rich plasma constitutes an effective and safe method supporting the treatment of chronic and hard-to-heal wounds. Its use can lead to the acceleration of the healing process, an increase in the rate of complete wound closure, and an improvement in the patients’ quality of life.